Uncertainty in artificial intelligence : proceedings of the Ninth Conference (1993) : July 9-11, 1993, the Catholic University of America, Washington, D.C. - Heckerman, David E.; Mamdani, Abe (Morgan Kaufmann Publishers, 1993)
Uncertainty in Artificial Intelligence.